The glorious forest that fire built - Neil, Ginny (Amicus Ink, 2023)
"A wildfire roars through the forest, leaving nothing but ashes until seeds sprout from deep below. A lyrical cumulative nonfiction story about forest succession, this narrative nonfiction picture book shows how the forest slowly grows back over many years. Life science-based back matter explains the timeline of the forest cycle in more detail"--